ANALISIS KESULITAN GURU DALAM MENERAPKAN PEMBELAJARAN DENGAN PENDEKATAN SAINTIFIK - Lisa Rahma Yanti; Zariul Antosa; M. Jaya Adiputra (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
The scientific approach is one of the methods that must be used in learning in the 2013 curriculum, but in reality not all teachers can apply a scientific approach to every learning process. This is because teachers still have difficulty applying the scientific approach, and some still do not understand the concept of each step of the scientific approach. Descriptive qualitative research aims to identify, and then collect, the factors of teacher difficulties in using learning with a scientific approach in SD Negeri 30 Pekanbaru with data collection techniques through observation and interviews and documentation using data analysis techniques Reduce data. the results showed that the teachers at Pekanbaru 30 Elementary School still had difficulty implementing various activities in a scientific approach. This is evident from several scientific approaches that have not yet been carried out, e.g. For example, survey activities in klass I, II, III, IV during the first and third observations and class V on the first observation were not carried out. No experimental activities were also carried out in class II and III of the first and third surveys. Likewise, in the second observation no communication activities were carried out in class I, in class II in each observation and in class III in the first and second observations